"[...] ja miłości mojej, która się rozkłada, treść i kształt boski wiernie chowam w sobie" - o pewnym dysonansie słów kilka - Urbańska, Monika (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2008)
Some can call this theme as perverse. For many people death was theme of taboo. People was affraid o f thinking and talking about it. Word “ to die” was replaced by noumerous euphemisms like: to sleep, go to the Lord, to leave. Saying about rating body was a scandal thing. But some of authors didn’t affraid to touch on the subject. This article present three poems which unite two themes: of death and of love: Carrion and After death remorse of Charles Baudelaire and Beautiful Maud of Maria Konopnicka. In Baudelaire’s poems we have a discordance between feeling of love to woman and wishing her to die. Ovcrmore, Baudelaire describes process of rating of a body with extreme precision, differently than Maria Konopnicka in Beautiful Maud. A dominant of the poem is love stonger than death, howerver it brings moral, estetical and ethical conflict.